Pengaruh Green Product Terhadap Minat Pembelian Ulang (Studi pada Produk Lampu LED Merek PHILIPS) - Al Lathifah, Aisyah Rizki; Widyastuti, Dominica A. (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
The purpose of this research is to examine the Philips LED lamp product known as Green Product and intention in the purchase of the product. Sampling method using Accidental Sampling technique with 110 respondents who are consumers of Philips LED Products brand. In this study using Simple Linear Regression Analysis. Hypothesis of this research is Green Product have positive and significant effect to intention of repurchase.